Improvement of Façades' Sound Insulation of Schools near the Bergamo - Orio al Serio International Airport: Case Study. Issue 2 (June 2015) - Torchia, Francesca; Ricciardi, Paola; Scrosati, Chiara; Scamoni, Fabio
In recent years the acoustic qualification of buildings has gained more and more importance at international level. Building renovation is one of the most common ways to improve the acoustic quality of the existing buildings; in particular, schools buildings are the ones that need more attention. In this context, the sound insulation requirements, especially for buildings near airport zones, play a role of primary importance. This paper analyses the data of a campaign of inspections and on-site measurements of façade sound insulation, concerning five public school buildings, close to the international airport of Bergamo - Orio al Serio. The analysis consisted in checking the sound insulation of buildings, after selecting classrooms with common characteristics, based on an accurate preliminary investigation involving more than 395 different characteristics of frames and glass windows. After having determined the D 2 m, nT, w, the most appropriate technological solutions for a refurbishment project were determined. Finally, the improved façade sound insulation was verified. The refurbishment project took place in 15 classrooms, characterised by a pre-treatment D 2 m, nT, w lower than 38 dB. Experimental post-treatment results showed that all classrooms satisfied the required basic performance of D 2 m, nT, w, and 13 of them fulfilled the high performance requirement of 43 dB, established in the Italian acoustic classification.